E(x,y,z) = qk·< ( (e^{ln(a)·x}+(-1))/x ) , ( (e^{ln(a)·y}+(-1))/y ) , ( (e^{ln(a)·z}+(-1))/z ) >
E(0,0,0) = qk·< ln(a) , ln(a) , ln(a) >
div[ E(x,y,z) ] = qk·( ...
... ( (e^{ln(a)·x}+(-1))/x )·ln(a)+( ln(a)/x )+(-1)·( (e^{ln(a)·x}+(-1))/x^{2} ) +..
... ( (e^{ln(a)·y}+(-1))/y )·ln(a)+( ln(a)/y )+(-1)·( (e^{ln(a)·y}+(-1))/y^{2} ) +...
... ( (e^{ln(a)·z}+(-1))/z )·ln(a)+( ln(a)/z )+(-1)·( (e^{ln(a)·z}+(-1))/z^{2} ) ...
... )
div[ E(0,0,0) ] = 3qk·( ln(a) )^{2}
No hay comentarios:
Publicar un comentario